Knowledge used when orchestrating mathematical discourses – doing, guiding and requesting - Drageset, Ove Gunnar (NOMAD Nordic Studies in Mathematics Education, 2014)
There is a need to understand more about which types of knowledge teachers use when orchestrating mathematical discourses. This article combines models for mathematical knowledge for teaching with a recent framework that describes the actions that teachers typically use during classroom discourses in mathematics. By looking into what knowledge each action demands from the teacher, three areas related to mathematical knowledge for teaching are described: doing, guiding and requesting. Doing describes different ways the teachers are doing the mathematical work themselves. Guiding describes how the teachers help, while leaving most of the work to the students. Requesting describes different ways teachers asked the students to explain or contribute to the discourse.